Social and Ecological Cost Analysis of Hydropower Development in Kerinci Seblat TNKS Conservation Area - Fernanda, Hengki (Brida Provinsi Jambi, 2025)
This research explores the social and ecological impacts of hydropower development in the Kerinci Seblat TNKS, an important conservation area in Indonesia. Although hydropower is promoted as a green investment solution for meeting national energy needs, there are conflicts between environmental interests, economic growth, and improving community welfare. Few previous papers have examined and studied in depth the effectiveness of conservation policies involving local wisdom and community welfare in the context of infrastructure development. This paper uses the literature review method and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach to analyze the socio-economic impacts and environmental conflicts related to hydropower development. The search shows that hydropower development has the potential to damage ecosystems and cause social tensions, so an inclusive and adaptive policy approach is needed. This paper indicates that conservation policies that integrate the perspectives of local communities to achieve sustainable development without sacrificing ecosystems and social welfare.